Strengthening the Role of Midwives in Adolescent Reproductive Health Education - Nonik Ayu Wantini; Tutik Hidayati (PT Bukuloka Literasi Bangsa, 2025)
Adolescent reproductive health is an important issue in public health development, given that adolescence is a transitional phase that is vulnerable to various physical, psychological, and social health problems. The low level of knowledge and awareness among adolescents regarding reproductive health requires the active role of health workers, especially midwives, in providing effective and sustainable education. This study aims to analyze in depth the role of midwives in strengthening adolescent reproductive health education through a qualitative literature review approach. Data were obtained from ten relevant national and international scientific articles, then analyzed using content analysis techniques to identify the main themes related to the role, challenges, and effectiveness of midwives in promoting reproductive health. The results of the study show that midwives have a multidimensional role as educators, counselors, facilitators, and community mobilizers who contribute to improving literacy and healthy reproductive behavior among adolescents. Factors supporting success include an empathetic communication approach, policy support, and cross-sector collaboration through programs such as Posyandu Remaja (Adolescent Health Posts) and Generasi Berencana (Family Planning Generation). This study concludes that strengthening midwives' educational competencies and integrating digital technology into counseling can be effective strategies for expanding the reach and impact of adolescent reproductive education. This study is expected to serve as a basis for the development of midwifery curricula and adolescent health promotion policies in the future. Keywords: midwifery, adolescent reproductive health, health education, literature review, adolescent empowerment.